PENGARUH PENERAPAN ENTERPRISE RESOURCE PLANNING TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Ruby Ketsiama Meijer P; Hendra Gunawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study aims to examine the effect of enterprise resource planning implementation on the performance of manufacturing companies moderated by the size of companies listed on the IDX period 2013-2015. Company size is seen through sales and total assets. Samples were taken by using purposive sampling and meeting the sample criteria. The analysis technique used in this research is multiple regression analysis. The results show that the implementation of enterprise resource planning significantly affects the company's performance is reinforced by high sales level and also affect the company's performance significantly reinforced by a large asset. The high sales and total assets can improve the performance of companies implementing ERP. Both of these factors have a significant influence. The results of this study are expected to add to the research literature on the factors that strengthen the performance of manufacturing companies that implement ERP. Future research can change the size of the company viewed from the income or the number of employees.Keywords: Enterprise performance, enterprise resource planning, sales, total assets